An investigation of the roles of geomagnetic and acoustic cues in whale navigation and orientation - Allen, Ann Nichole (Massachusetts Institute of Technology, 2013)
Thesis (Ph. D.)--Joint Program in Oceanography/Applied Ocean Science and Engineering (Massachusetts Institute of Technology, Department of Biology; and the Woods Hole Oceanographic Institution), 2013. Cataloged from PDF version of thesis. Includes bibliographical references. Many species of whales migrate annually between high-latitude feeding grounds and low-latitude breeding grounds. Yet, very little is known about how these animals navigate during these migrations. This thesis takes a first look at the roles of geomagnetic and acoustic cues in humpback whale navigation and orientation, in addition to documenting some effects of human-produced sound on beaked whales. The tracks of satellite-tagged humpback whales migrating from Hawaii to Alaska were found to have systematic deviations from the most direct route to their destination. For each whale, a migration track was modeled using only geomagnetic inclination and intensity as navigation cues. The directions in which the observed and modeled tracks deviated from the direct route were compared and found to match for 7 out of 9 tracks, which suggests that migrating humpback whales may use geomagnetic cues for navigation. Additionally, in all cases the observed tracks followed a more direct route to the destination than the modeled tracks, indicating that the whales are likely using additional navigational cues to improve their routes. There is a significant amount of sound available in the ocean to aid in navigation and orientation of a migrating whale. This research investigates the possibility that humpback whales migrating near-shore listen to sounds of snapping shrimp to detect the presence of obstacles, such as rocky islands. A visual tracking study was used, together with hydrophone recordings near a rocky island, to determine whether the whales initiated an avoidance reaction at distances that varied with the acoustic detection range of the island. No avoidance reaction was found. Propagation modeling of the snapping shrimp sounds suggested that ...